2022
DOI: 10.3390/molecules27175528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ZnO Nanofiller on Structural and Electrochemical Performance Improvement of Solid Polymer Electrolytes Based on Polyvinyl Alcohol–Cellulose Acetate–Potassium Carbonate Composites

Abstract: In this study, a solution casting method was used to prepare solid polymer electrolytes (SPEs) based on a polymer blend comprising polyvinyl alcohol (PVA), cellulose acetate (CA), and potassium carbonate (K2CO3) as a conducting salt, and zinc oxide nanoparticles (ZnO-NPs) as a nanofiller. The prepared electrolytes were physicochemically and electrochemically characterized, and their semi-crystalline nature was established using XRD and FESEM. The addition of ZnO to the polymer–salt combination resulted in a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…One of the possible explanations for the expansion of the ESW with the introduction of inorganic filler could be attributed to the generation of insulating oxidized species that passivates the electrode surface at high voltages [37b] . Another explanation is the intimate binding interaction of the ceramic fillers with the polymer‐salt chain, altering the polymer physical properties and hindering the decomposition of electrolytes and thereby expanding the ESW [95b] …”
Section: Strategies Toward Advanced Solid‐state Zibs and Aibsmentioning
confidence: 99%
“…One of the possible explanations for the expansion of the ESW with the introduction of inorganic filler could be attributed to the generation of insulating oxidized species that passivates the electrode surface at high voltages [37b] . Another explanation is the intimate binding interaction of the ceramic fillers with the polymer‐salt chain, altering the polymer physical properties and hindering the decomposition of electrolytes and thereby expanding the ESW [95b] …”
Section: Strategies Toward Advanced Solid‐state Zibs and Aibsmentioning
confidence: 99%
“…The rise of conductivity values resulted from an increase in the number of charge carriers and mobility by rising ZnO concentration. An extra loading of ZnO NPs caused extra accumulation of ZnO NPs at the surface of the film which might decrease its conductivity as the charge carrier mobility decreased [63]. For 10 wt%, it was found that the conductivity reached a maximum value of 1.2 × 10 −7 Sm −1 .…”
Section: Dielectric Studiesmentioning
confidence: 99%
“…Methylcellulose (MC) is a common biopolymer synthesized by substituting the OH groups of cellulose with methyl groups [17][18][19]. Thus, MC contains multiple hydrophobic methoxy groups connected to its hydrophilic polysaccharide backbone.…”
Section: Introductionmentioning
confidence: 99%